Profile of self-confidence among children aged 5-6 years based on the adoption of an early childhood self-confidence instrument - aulya septy rahmasari; Henny Indreswari; Khairul Bariyyah; M Ramli; Zamroni Zamroni (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
The purpose of this study was to adapt and apply a contextual and behavior-based self-confidence instrument through the Rabbit Life Creative Dance activity for children aged 3–4 years. Self-confidence is an important aspect in the social-emotional development of early childhood that plays a role in the ability to explore, interact, and adapt to the environment. However, measuring self-confidence in early childhood still faces limitations, especially because children are not yet able to express their psychological condition verbally. Therefore, an instrument is needed that is appropriate to the characteristics of child development. This study used a descriptive approach with an instrument adaptation procedure that refers to the principle of behavioral observation. The instrument used was adapted from the child self-confidence scale developed by Susan Harter and Judy Haltiwanger, then adjusted to the activities in the creative dance used. The research subjects were children aged 3–4 years who were selected purposively. Data collection techniques were carried out through observation, and the data were analyzed descriptively. The results of the study indicate that the developed instrument can be used practically in learning activities and is able to describe variations in children's self-confidence, which include aspects of courage, initiative, and emotional resilience. Thus, this instrument can be an alternative contextual and relevant measurement tool for use in early childhood education.